Accessing HIV services in Botswana: perspectives of men who have sex with men and other stakeholders - Kgosiekae Maxwell Matlapeng; Gbotemi Bukola Babatunde; Netsai Bianca Gwelo; Olagoke Akintola (Taylor & Francis Group, 2023)
Background Men who have sex with men (MSM) represent an increasing number of new HIV infections in Botswana. Many in Botswana still hold discriminatory views against people who engage in same-sex practices. While it is well documented that stigma and discrimination undermine efforts to prevent HIV, the literature about the perception and experiences of discrimination against MSM in accessing HIV services in Botswana is scant. Objective(s) In this study, we sought to explore the perception and experiences of discrimination against MSM to improve access to HIV services and reduce discrimination against this marginalised population. Methods We employed a descriptive qualitative design using purposive sampling to recruit 20 MSM and 12 stakeholders (six policy-makers and six service providers) involved in implementing HIV/AIDS interventions in Botswana. We conducted semi-structured interviews with participants. All data were audio-recorded, transcribed, translated into English and analysed using thematic analysis. Results The findings of this study show that MSM experience discrimination at the policy, healthcare system and community levels, which undermines their ability to seek HIV services. The participants reported that MSM are excluded from HIV policies and targeted HIV services. They reported a scarcity of trained personnel, poor access to HIV information, condoms, lack of treatment services targeted at MSM and negative attitudes directed towards MSM by service providers and other users. The participants also reported that they are excluded from community interventions and experience negative attitudes from community and family members. Conclusion Discrimination against MSM undermines the ability of HIV interventions to address MSM sexual health needs. The findings indicate the importance of enabling MSM to overcome discrimination to seek HIV services. Also, there is a need to further explore discrimination against MSM by service providers within the healthcare settings and ways to improve their understanding of male same-sex practices.